Lower Susceptibility of Laser-irradiated Ti-15Mo Surface to Methicillin-resistant Staphylococcus aureus Cells Adhesion - Guastaldi, Fernando Pozzi Semeghini; Foggi, Camila Cristina De; Santana, Luis Carlos Leal; Vaz, Luis Geraldo; Vergani, Carlos Eduardo; Guastaldi, Antonio Carlos (ABM, ABC, ABPol, 2019)
Extensive data reported the influence of the physicochemical properties on the bacterial adhesion in biomaterials, of which surface roughness of titanium (Ti) can dictates methicillin-resistant Staphylococcus aureus (MRSA) adhesion to orthopedic implants. Herein, we investigated the influence of the Yb:YAG laser texturing of titanium-15molybdenum (TiMo-L) surface on the MRSA (ATCC #33591) cells adhesion and viability. The physicochemical properties and antibacterial performance of TiMo-L were compared to samples of laser-irradiated pure titanium (Ti-L). Polished samples (Ti-P and TiMo-P) were used as controls. Laser textured surfaces presented a high degree of hydrophilicity, an irregular-shaped cavity and a typical microstructured pattern, compared to the polished substrates. The laser irradiation reduced the peaks of molybdenum (Mo) in the surface of Ti-15Mo alloy, which is explained, at least in part, by the difference between the melting point of Ti (1.668 ºC) and Mo (2.623 ºC). Laser texturing raised the MRSA cells viability and statistically increased the bacterial adhesion to pure Ti (P < 0.01; Wilcoxon-Signed rank test) and Ti-15Mo alloy (P < 0.001; Paired t test). The TiMo-L surface was significantly less susceptible to MRSA cell adhesion compared to Ti-L substrate (P < 0.001; Paired t test).
Keywords: Biological adhesion; methicillin-resistant Staphylococcus aureus; surface treatment; titanium and alloys